The Determinants of Diarrheal Disease in the Community with Homestay Tourism: A Mixed-Methods Research - Borwornsom Leerapan (2022)
Background: Diarrheal epidemics in communities with homestay tourism can be more than health problems-they also can damage the local economics. Objective: This study investigated health determinants in a homestay village and its community resources that could contribute to diarrheal prevention and control. Methods: This observational study employed a mixed-methods research design. Study population included all residents of the homestay village of Khok Kong (N = 557). Quantitative data were obtained by a cross-sectional survey using a simple random sampling (n = 47), and analyzed by chi-squared test and multivariate logistic regression. Quantitative data were collected by participant observations, and analyzed by content analysis. Results: 23% of the samples experienced acute diarrhea in the last three months, which are associated with habit of washing hands before meals (odds ratio [OR] = 0.16, P = 0.010) and with female gender (OR = 0.19, P = 0.025). The relationship remains significant after controlling for gender (OR = 0.22, P = 0.048). Statistical analysis suggests the villagers with good hand hygiene less likely had diarrhea. No evidence of relationships between types of food and drinking water and diarrhea is found in this community. Content analysis revealed “adequate hygiene for cooking and eating within households”, “poor sanitization of local restaurants and grocery stores”, “good health literacy”, and “community potentials for self-development”. Conclusions: Statistical findings from the survey are matched with results from content analysis, which revealed that diarrheal prevention was empowered in most households. Outside the households, however, food safety approved to be insufficient and could be a potential source of diarrheal widespread.